Hi there!
We can begin by deriving an equation for the orbital radius.
For an object orbiting the earth, it is experiencing a centripetal force due to the force of gravitation.
Recall Newton's Law of Universal Gravitation:
[tex]F_g = \frac{Gm_1m_2}{r^2}[/tex]
G = Gravitational Constant (6.67 × 10⁻¹¹ Nm²/kg²)
m = masses (kg)
r = radius (m)
This is equivalent to the satellite's centripetal force experienced:
[tex]F_c = \frac{m_sv^2}{r}[/tex]
[tex]m_s[/tex] = mass of satellite (kg)
v = velocity (m/s)
r = radius (m)
Set the two equal, and rearrange for the orbital radius of the satellite.
[tex]\frac{Gm_sm_p}{r^2} = \frac{m_sv^2}{r}\\\\\frac{Gm_p}{r} = v^2\\\\r = \frac{Gm_p}{v^2}[/tex]
Notice that the orbital radius of the satellite does NOT depend on the satellite's mass. (we canceled it out).
Now, plug in the given values.
[tex]r = \frac{(6.67\times 10^{-11})(6\times 10^{20})}{17000^2} = \boxed{138.478 m}[/tex]